KETRAMPILAN KOMUNIKASI GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI KELOMPOK BERMAIN MAHARDIKA - Cintami Farmawati; Siti Nureliza (JURNAL LENTERA ANAK, 2020)
The purposive of this research to know the communication skills of teacher in increasing the learning motivation of student in playgroup Mahardika. The method of research used is qualitative with descriptive approaches. Research subjects consisted of three teachers and fifteen student in playgroup Mahardika. Data collection techniques through observation and in-depth interviews. The data analysis technique used descriptive qualitative. Based on interviews and observations at the research location, this study resulted in several findings. First, the importance of teacher communication skills in increasing early childhood learning motivation, through various communication skills mastered by teachers can make early childhood happy and enthusiastic in learning. Teacher's main and very important communication skills are listening and understanding, having good emotional intelligence, selecting the right media for communication and empathy. Second, the collaboration between teachers and parents of students in increasing children's learning motivation. Teacher communication skills are not only with students but also need communication skills between teachers and parents of students so that children's success is achieved in learning.